A FRET-based real-time PCR assay to identify the main causal agents of New World tegumentary leishmaniasis. - Pablo Tsukayama; Jorge H Núñez; Maxy De Los Santos; Valeria Soberón; Carmen M Lucas; Greg Matlashewski; Alejandro Llanos-Cuentas; Marianela Ore; G Christian Baldeviano; Kimberly A Edgel; Andres G Lescano; Paul C F Graf; et al. (Public Library of Science (PLoS), 2013)
In South America, various species of Leishmania are endemic and cause New World tegumentary leishmaniasis (NWTL). The correct identification of these species is critical for adequate clinical management and surveillance activities. We developed a real-time polymerase chain reaction (PCR) assay and evaluated its diagnostic performance using 64 archived parasite isolates and 192 prospectively identified samples collected from individuals with suspected leishmaniasis enrolled at two reference clinics in Lima, Peru. The real-time PCR assay was able to detect a single parasite and provided unambiguous melting peaks for five Leishmania species of the Viannia subgenus that are highly prevalent in South America: L. (V.) braziliensis, L. (V.) panamensis, L. (V.) guyanensis, L. (V.) peruviana and L. (V.) lainsoni. Using kinetoplastid DNA-based PCR as a gold standard, the real-time PCR had sensitivity and specificity values of 92% and 77%, respectively, which were significantly higher than those of conventional tests such as microscopy, culture and the leishmanin skin test (LST). In addition, the real-time PCR identified 147 different clinical samples at the species level, providing an overall agreement of 100% when compared to multilocus sequence typing (MLST) data performed on a subset of these samples. Furthermore, the real-time PCR was three times faster and five times less expensive when compared to PCR - MLST for species identification from clinical specimens. In summary, this new assay represents a cost-effective and reliable alternative for the identification of the main species causing NWTL in South America.